Towards Effective AI Support for Developers: A Survey of Desires and Concerns - Khemka, Mansi; Houck, Brian (ACM Queue, 2024)
"Towards Effective AI Support for Developers: A Survey of Desires and Concerns," co-authored with Mansi Khemka, explores developers' perspectives on AI integration in their workflows. This study prioritizes developers' voices, revealing their top desires for AI assistance and major concerns. By conducting a comprehensive survey among 791 Microsoft developers, the research identifies key areas where AI can enhance productivity and highlights significant apprehensions about AI's practicality and reliability. The findings provide actionable insights for product teams and leaders to create AI tools that truly support developers' needs.